Analisis Kimia dan Tingkat Kesukaan terhadap Abon Daun Singkong dengan Perlakuan Lama Perebusan - Nela Eska Putri; Nanda Triandita; Maya Indra Rasyid; Reno Irwanto; Didit Hadisiswaya; Nyimas Rupiah; Supriyadi Supriyadi (Universitas Teuku Umar, 2020)
Cassava leaves have a high nutritional content, including carbohydrates, proteins, fats and minerals.Cassava leaves can be processed into chopped dry food like a floss. The treatment of long time boiling cassava leaves (P1=0, P2=10, P3=20, and P4=30 minutes) was studied to observe the characteristics of the formed cassava leaf floss, including water content (%), ash content (%), pH, antioxidant capacity (%), and sensory value. The result showed that treatment of long time boiling cassava leaves 10-20 minutes did not significantly affect the water content, but boiling for 30 minutes had a significant effect on the resulting water content (13.52%). Boiling time did not significantly affect ash content, pH, and antioxidant capacity of cassava leaf floss. Based on the analysis of the hedonic ranking test, it showed that the P1 was the most preferred by the panelists. P1 has a moisture content of 5.16 ± 0.32%, an ash content of 8.85 ± 2.95%, a pH of 5.76 ± 0.16, and an antioxidant capacity of 66.47%.